Designed NiMoC@C and NiFeMo2C@C core-shell nanoparticles for oxygen evolution in alkaline media - Li, Xiang; Giordano, Cristina (Frontiers in Chemistry, 2023)
Electrochemical water splitting is one of the most promising and clean way to produce hydrogen as a fuel. Herein, we present a facile and versatile strategy for synthesizing nonprecious transition binary and ternary metal-based catalysts encapsulated in a graphitic carbon shell. NiMoC@C and NiFeMo2C@C were prepared via a simple sol-gel based method, for application in Oxygen Evolution Reaction (OER). The conductive carbon layer surrounding the metals was introduced to provide a continuous pathway for facile electron transport throughout the catalyst structure. This multifunctional structure, show synergistic effects, possess a larger number of active sites, a fast electron transport and enhanced electrochemical durability. Structural analyses indicated that the all metallic phases were encapsulated in the graphitic shell. Experimental results demonstrated that the optimal core-shell material NiFeMo2C@C exhibited the best catalytic performance for the OER in 0.5 M KOH, reaching a current density of 10 mA cm-2 at low overpotential of 292 mV for the OER, superior to the benchmark IrO2 nanoparticles. The good performances and stability of these OER electrocatalysts, alongside an easily scalable procedure makes these systems ideal for industrial purposes.